The Role of the Environmental Agency in Waste Management: A Qualitative Study in West Aceh District - Winda Habsi; Darmawan Darmawan; Ernawati Ernawati; Wintah Wintah; Yulizar Kasma (An Idea Health Journal, 2026)
Introduction: The rapid growth of population and economic activity has exacerbated waste management challenges in Indonesia, including in West Aceh Regency. The imbalance between waste generation and the capacity of existing management systems has led to waste accumulation in various locations, particularly in densely populated areas. This study aims to examine the role of the Environmental Agency (DLH) in addressing waste congestionand to identify the supporting and constraining factors that influence the implementation of waste management policies in West Aceh Regency. A qualitative descriptive design with a phenomenological approach was employed to gain an in-depth understanding of the experiences and perceptions of waste management stakeholders. Data were collected through in-depth interviews,field observations, and document review using purposive sampling, involving DLH officials, sanitation workers, and community members. Data analysis was conducted through iterative processes of reduction, presentation, and verification. The findings indicate that the West Aceh DLH plays a strategic role in waste management through the implementation of a controlled landfill system, community education on waste segregation, and strengthened cross- sectoral collaboration such as waste bank initiatives and communal clean-up activities. However, policy effectiveness remains constrained by limitedfacilities and infrastructure, insufficient human resources, and low community participation in fee payment and waste sorting practices. In conclusion, successful waste management in West Aceh requires greater synergy among institutional capacity, regulatory support, and community-based social awareness to ensure sustainable waste governance.